Correction: Liu et al. LeGRXS14 Reduces Salt Stress Tolerance in Arabidopsis thaliana. Plants 2023, 12, 2320 - Lulu Liu; Xiaofei Li; Mengke Su; Jiaping Shi; Qing Zhang; Xunyan Liu (Plants, 2023)
The authors wish to correct the following error in the original paper [...]